First Language Attrition as a Function of Age at Onset of Bilingualism: First Language Attainment of Turkish–English Bilinguals in the United Kingdom. Issue 1 (17th September 2018) - Karayayla, Tuğba; Schmid, Monika S.
Abstract : This investigation aimed to provide insights into the controversial debate on the role that age at onset of bilingualism plays in human language capacity with a focus on what it entails for first language (L1) attrition. L1 performance of Turkish immigrants ( n = 57) in the United Kingdom with age at onset ranging between 7 and 34 years was compared to that of Turkish monolingual controls ( n = 29) across two linguistic properties: structural complexity and accent. Findings generally showed that although the immigrants achieved nativelike proficiency with respect to the overall structural complexity of their L1, this was not the case for accent as those with an earlier age of onset were less likely to sound like native Turkish speakers. We discuss these findings in relation to two competing theoretical models of age effects and suggest that attrition data need to be better accommodated within these models. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible via the IRIS Repository athttps://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki . Abstract :